Kryteria sprawowanej przez sądy administracyjne kontroli decyzji uznaniowych - Artymionek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article concerns the criteria of review adopted by administrative courts to examine decisions issued by public authorities at their administrative discretion. The author presents views of legal commentators and judicial decisions with respect to administrative law and the case law of administrative courts, specifically investigating the current views. The author reflects on whether it is essentially admissible to review a discretionary decision. He also shows the differences and similarities between a mandatory decision and a discretionary decision and answers the following question: Is it admissible to review a discretionary decision by an administrative court on the basis of the criterion of expediency? Is the court only authorized to consider the criterion of legality?According to the main conclusions of the article, there are no differences between a mandatory decision and a discretionary decision as far as the review by the administrative courts is concerned; the criterion of expediency is permitted if such a criterion emanates from the regulations empowering the authority to make discretionary decisions; it has also been observed that administrative courts increasingly expand the review capacity to ensure compliance with the law, so that any such review could also be used to verify the correctness of the discretionary decision which has been issued.
Keywords: discretionary decision; administrative decision; administrative court review; criteria of review adopted by administrative courts; public authority supervision